Evaluating Inquiry-Based Learning as A Pedagogical Strategy in Achieving Outcome-Based Education Targets in EFL Writing (Tamaddun, 2025)
This study aimed to evaluate the effectiveness of the Inquiry-based Learning approach in achieving Outcome-based Education targets in teaching writing skills as a foreign language. A quantitative method was employed, using a one-group pre-test and post-test design. The participants consisted of 34 students, who participated in writing tasks with different topics administered at the pre-test and post-test stages. The data were analyzed using the Wilcoxon Signed Rank Test, due to the non-parametric distribution. The analysis revealed significant improvement in students’ writing skills, including paragraph structures, idea development, lexical precision, and academic language style. These findings indicate that Inquiry-Based Learning effectively fosters active student engagement, promotes self-directed exploration, and enhances the ability to strengthen written expressions. Based on the results, it can be concluded that Inquiry-based Learning is a relevant and effective strategy for achieving Outcome-Based Education goals in the context of EFL writing competencies.